A laboratory study of the elastic anisotropy in the Mancos shale at seismic frequencies - Mikhaltsevitch, Vassili; Lebedev, M.; Gurevich, B. (2016)
We measured the Young's modulus dispersion, P-wave anisotropy and extensional attenuation in two Mancos shale samples as a function of water saturation at frequencies between 0.1 Hz and 100 Hz. The samples were cored along vertical and horizontal directions with respect to the formation bedding and saturated at five different humidities ranging from 9% to 97.5%. The laboratory measurements demonstrate a reduction of the Young's modulus caused by a sample softening with increasing saturation. We also showed that the modulus dispersion, which occurs when the samples are saturated at a relative humidity of 97.5 %, can significantly decrease the P-wave anisotropy.